Method for predicting dynamic loads for a health monitoring system for subway tracks - Jauregui-Correa, Juan Carlos; Morales-Velazquez, Luis; Otremba, Frank; Hurtado-Hurtado, Gerardo (Frontiers in Mechanical Engineering, 2022)
This paper presents a method for processing acceleration data registered on a train and determining the health condition of a subway’s substructure. The acceleration data is converted into a dynamic force by applying a transfer function defined using the Empirical Mode Decomposition Method. The transfer function was constructed using data produced on an experimental rig, and it was scaled to an existing subway system. The equivalent force improves the analysis of the dynamic loads that affect the substructure of railroad or subway tracks. The acceleration data and the estimated forces are analyzed with the Continues Wavelet Transform. The equivalent force data facilitates the application to a health monitoring system and simplifies the development of predictive maintenance programs for the subway or railroad operators. This method better-identified cracks in the substructure than only using the acceleration data.